Inulin and Polydextrose as Fat Replacers in Non-Fat Dahi: Physicochemical, Textural and Sensory Properties - Shinde, Dnyaneshwar Ramesharao; N., Veena; Surendra Nath Battula, Surendra Nath (Indian Journal of Dairy Science, 2025)
The potential of inulin and polydextrose as a fat replacer in fat-free dahi was evaluated in this study. The effects of adding combination of different type of inulin with polydextrose (1:1) on the physicochemical, texture and sensory properties of non-fat dahi were investigated during storage. Compared with control non-fat dahi (CND), the addition of combination of inulin and polydextrose increased the solid content, pH, viscosity, firmness value and water holding capacity of non-fat dahi, however, no such difference was observed between control full-fat dahi (CFA) and dahi added with fat replacers. Sensory scores of dahi added with fat replacers were similar to that of CFD while lowest acceptability scores were observed for CND. The sensory attributes and physicochemical properties such as firmness, water holding capacity and pH value decreased significantly after 6 days of storage in both control dahi and dahi added with fat replacers. The results indicated that combination of inulin and polydextrose may be used as alternative sources of fat replacer to enhance the quality attributes of non-fat dahi.